FAKTOR YANG MEMPENGARUHI KEPUASAN DAN LOYALITAS KONSUMEN RUMAH MAKAN LANGENSARI - Fauzia, Syifa; Relawati, Rahayu; Ningsih, Gumoyo Mumpuni (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2020)
Restaurant is an interesting business, because of the high profits. The high competition between culinary businesses can encourage businesses to reach consumer satisfaction, in order to get their loyalty. The purpose of this study was to analyze the factors affecting the consumer satisfaction and loyalty at Langensari Restaurant. Accidental sampling was used to take 76 consumers as the research sample. The Structural Equation Model (SEM) and Customer Satisfaction Index (CSI) were used to analyze the data. The study result shows that consumers visiting Langensari Restaurant were very satisfied with the score of 93,57 percent. It means that the restaurant performance in the form of products, fixed prices, places, and services were fulfill the consumers expectation. Price and place affected customer satisfaction, while product and service did not affect customer satisfaction. Satisfaction had a positive effect on loyalty. The higher the level of cunsomer satisfaction, the higher the loyalty. Products, prices, services, and places also indirectly influence loyalty. Restaurants should improve the performance in terms of products, prices, services, and places. They need to be improve the flavor, price affordability, and toilet cleanliness.